PEMBERDAYAAN PETANI RUMPUT lAUT OLEH DINAS KElAUTAN DAN PERIKANAN KABUPATEN BUTON PROVINSI SULAWESI TENGGARA - Muh. Feisal Ariwiguna Asimu; Rian Dwi Hapsari (ipdn, 2018)
The potential of Indonesian sea is very extraordinary, including seaweed. Seaweed has great potential and can be cultivated by Indonesian people so that increase employment. Of course in this case need support from the community and the local government. The purpose of this study was to find out the efforts made by the government and obstacles in the empowerment of seaweed farming communities in Kamelanta Village. The author uses descriptive research methods with an inductive approach, data collection techniques used are interviews, observation and documentations. Some of the obstacles that occur in seaweed cultivation are the excessive dependence of seaweed farmers on the government, lack of understanding of business people on empowerment and lack of infrastructure such as modern factories in supporting the processing of products that are more economically valuable. Based on the results of the study, there were several efforts at the Marine and Fisheries Service such as: 1) inviting foreign investors, 2) creating programs such as saffver for sustainable development by cultivators to process seaweed as a form of food security. Keywords: empowerment, seaweed farmers, seaweed